ANXIOLYTIC ACTIVITY OF OCIMUM SANCTUM LEAF EXTRACT - Chattopadhyay, R.R. (Medknow Publications & Media Pvt Ltd, 1994)
The anxiolytic activity of Ocimum sanctum leaf extract was studied in mice. O.sanctum leaf extract produced significant anxiolytic activity in plus – maze and open field behaviour test models. The effect was compared with diazepam, a standard antianxiety drug.